Study on Coaches’ and Athletes’ Attitude Towards the Consumption of Doping Substances - BERBECARU, Claudia; VASILE, Luciela; CROITORU, Doina; STĂNESCU, Monica (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2024)
Doping continues to attract the attention of specialists in the field of Sports Science due to its frequency of occurrence and the need for scientific substantiation of educational interventions. In all the conditional factors of doping behaviour, coaches and athletes are the key factors. Coaches are often identified as a potential enabler in athletes' doping, but precisely for this reason, they continue to be identified with their status as important potential agents in doping prevention. In turn, the athlete is the product of his own development and social-educational-cultural factors. The behavior of rejection or acceptance of the use of prohibited substances is determined by internal, subjective factors and external, social-environmental factors. An extensive model of risk factors, at international level, shows that interventions are needed at different levels for the educational effect to increase. In order to identify the attitude of coaches and athletes working in the Romanian sports system, between February and April 2022, online, with the help of Google forms, two questionnaires about anti-doping knowledge and attitudes were applied, one for athletes and one for coaches. The analysis of the results found that experienced coaches are better informed and have objective views on the impact of doping in sport. On the other hand, athletes resort to doping under peer pressure, lack of time required for training and as a result of competition pressure. Knowledge of these attitudinal peculiarities allows the formulation of recommendations on educational activities in the field of anti-doping education. Studiu privind atitudinea antrenorilor și sportivilor față de consumul de substanțe dopante. Fenomenul dopajului continuă să atragă atenția specialiștilor din domeniul Științei Sportului care urmare a frecvenței de apariție a acestuia și nevoii de fundamentare științifică a intervențiilor educative. În ansamblul factorilor condiționali ai comportamentului doping, antrenorii și sportivii reprezintă factorii esențiali. Antrenorii sunt adesea identificați ca un potențial factor favorizant în fenomenul de dopaj al sportivilor, dar tocmai din acest motiv, ei continuă să fie identificați și cu statutul de agenți potențiali importanți în prevenirea dopajului. La rândul său, sportivul este produsul propriei dezvoltări şi al factorilor sociali-educaţionali-culturali. Comportamentul de respingere sau de acceptare a folosirii substanţelor interzise este determinat de factorii interni, subiectivi şi factorii externi, sociali-ambientali. Un model extins al factorilor de risc, la nivel internațional, arată că intervențiile sunt necesare la diferite niveluri, pentru ca efectul educațional să sporească. Pentru identificarea atitudinii antrenorilor și sportivilor care activează în sistemul sportiv din România, în perioada februarie-aprilie 2022, online, cu ajutorul Google forms, au fost aplicate două chestionare despre cunoștințe și atitudini anti-doping, unul pentru sportivi și unul pentru antrenori. În urma analizei rezultatelor, s-a constatat că antrenorii cu experiență sunt mai bine informați și au opinii obiective privind impactul dopajului în sport. Pe de altă parte, sportivii apelează la dopaj la presiunea colegilor, a lipsei timpului necesar pentru pregătire și ca urmare a presiunii concursului. Cunoașterea acestor particularități atitudinale permite formularea unor recomandări privind activitățile educaționale în domeniul educației antidoping. Cuvinte-cheie: antrenori, sportivi, anti-doping, substanțe dopante Article history: Received: 2024 April 26; Revised 2024 August 16; Accepted 2024 August 28; Available online: 2024 August 30; Available print: 2024 August 30